Impact of Vaptans on Clinical Outcomes in Cirrhosis Patients: A Meta-Analysis of Randomized Controlled Trials - Li, Miao; Bi, Zhuofang; Huang, Zicheng (Frontiers in Pharmacology, 2019)
Background: Vaptans have been confirmed to mobilize ascites and improve hyponatremia in cirrhosis patients. However, the effects of vaptans on all-cause mortality, ascites-related complications, and adverse events in cirrhosis patients have not been fully determined. Objectives: To systematically evaluate the impact of vaptans on the clinical outcomes in patients with cirrhosis. Materials and Methods: A systematic review and meta-analysis was performed. The PubMed, Embase, and Cochrane’s Library electronic databases were systematically searched for randomized controlled trials (RCTs) investigating the clinical efficacy of vaptans in cirrhosis patients. The results were pooled with a random-effect model. Results: Eighteen RCTs containing 3,059 cirrhosis patients with ascites and/or hyponatremia were included. Meta-analysis showed that vaptans did not significantly affect the risk of all-cause mortality (RR: 1.02, 95% CI: 0.87 to 1.08, p = 0.83; I2 = 2%), consistent with studies with short-term (< 26 weeks) and long-term (≥ 26 weeks) follow-up durations. Additionally, vaptans did not affect the incidence of variceal bleeding (RR: 0.96, p = 0.86), showed a trend of reduced incidence of hepatic encephalopathy (RR: 0.86, p = 0.09), significantly reduced the incidence of spontaneous bacterial peritonitis (RR: 0.75, p = 0.03), but did not significantly affect the risk of hepatorenal syndrome or renal failure (RR: 1.09, p = 0.36). Vaptans did not affect the incidence of adverse events in cirrhosis patients. Discussion: Treatment with vaptans is not associated with improved survival in cirrhosis patients, although it may reduce the risk of hepatic encephalopathy and spontaneous bacterial peritonitis in these patients. The limitations of the current study include limited number of available studies, small sample sizes of the included studies, variations of baseline patient characteristics, and differences in the dose and duration of vaptans.